THE RULE OF LAW AND ACCESS TO JUSTICE: SOME HOME TRUTHS. (19th March 2018) - Elliott, Mark
Abstract : MISAPPREHENSIONS about the UK's constitution are ten-a-penny. Most prominent among them, perhaps, are the notions that the UK "has no constitution" and that fundamental rights cannot meaningfully exist without an "entrenched" or "written constitution". To that list of misunderstandings can now be added the ideas – brought to light by the Supreme Court's judgment in R. (UNISON) v Lord Chancellor [2017] UKSC 51, [2017] 3 W.L.R. 409 – that the judicial system, far from being a non-negotiable feature of any constitutional democracy, is nothing more than a public service, and that access to it can be regulated by the executive accordingly. To describe UNISON as a welcome corrective to such misconceptions would be to engage in rash understatement. In a tour de force that ought to be compulsory reading for every Minister and parliamentarian, the Court elucidates the true value of independent courts and tribunals, illuminates the common law's potential as a guarantor of basic rights, and reiterates an axiomatic set of constitutional home truths.